African Americans and Short-Term Outcomes after Surgery for Crohn’s Disease: An ACS-NSQIP Analysis - Arsoniadis, Elliot G. (J Crohns Colitis, 2017)
BACKGROUND: Previous reports on racial disparities in the treatment of Crohn’s disease [CD] in African American [AA] patients have shown differences in both medical and surgical treatments in this population. No study thus far has examined the effect of AA race on outcomes after surgery for CD. METHODS: Utilizing the National Surgical Quality Improvement Program [NSQIP] Participant User File [PUF] for the years 2005–2013, we examined the effect of AA race on postoperative complications in patients with CD undergoing intestinal surgery. RESULTS: AA patients had a significantly higher rate of complications overall compared to non-AA patients [23.5% vs 18.9%, p = 0.002]. Postoperative sepsis [10.9% vs 6.6%, p < 0.001] and surgical site infection [17.6% vs 14.8%, p = 0.037] were most significant. After adjustment for age, sex, preoperative disease severity and lifestyle factors [smoking], race remained a statistically significant factor in postoperative complication rate. Only after additional adjustment was made for comorbidities and American Society of Anesthesiologists class did race lose significance within our model. CONCLUSION: African Americans experience a greater amount of postoperative complications following surgery for Crohn’s disease. Preoperative disease management, addressing smoking status and control of comorbid disease are important factors in addressing the racial disparities in the surgical treatment of Crohn’s disease.